Perancangan Diorama Sebagai Media Promosi Toko Mainan Fabian Hot Wheels di Surakarta - Aditya Firmansyah, Baqoh; Henny Lukitasari, Evelyne; Yulianto, Arif (Universitas Sahid Surakarta, 2023)
Abstract Hot wheels are a type of miniature car with metal and plastic materials. Shapes and colours Design are made to resemble the original cars of many brands. The selling value of Hot Wheels products is the limited number of productions, so it makes them rare. Fabian Hot Wheels has been in the Hot Wheels product business for a long time and has become an alternative store for Hot Wheels products in Solo. It is due to the prices offered are relatively cheap. The rise of consumer interest in Hot Wheels car products has resulted in many similar competitors. This is indicated by the inclusion of Hot Wheels products at Gramedia and toy stores at the Mall. Efforts to attract new consumers and retain old customers require something exciting. Moreover, they have cultural and geographical values close to the surrounding community's values in the form of a Hot Wheels car track diorama. The design method for this diorama marketing media is data collection and interviews with related parties. Diorama as a promotional medium for hot wheels is expected to increase interest in Hot Wheels. Keywords Design, Diorama, Hot Wheels